ISOLATION AND CHARACTERIZATION OF ENDOPHYTIC BACTERIA IN SEVERAL FORAGE GRASS CULTIVARS - Hà, Nguyễn Thị Thu (Vietnam Journal of Biotechnology, 2011)
Four wild forage grass cultivars (Pennisetum purpureum, Pannicum maximum, Brachiaria mutica, Ischaemum rugosum) were collected in three provinces (Vinh Long, Dong Thap, Can Tho) of the Mekong Delta, Vietnam to isolate, identify, evaluate some good characteritics of these endophytes, determine nifH gene in nifrogen-fixing endophytes and sequence some good endophytes. The results showed that seventy-one bacterial isolates were isolated in several forage grass cultivars. However, 42 isolates were identified as endophytic bacteria using 16S rDNA analysis with specific primers. Thirteen endophytes with a good composite characteristics (high lAA biosynthesis, phosphate solubilization and fixing nifrogen) were detected based on biochemical tests. Among them, 7 endophytes in Nfb medium were identified as Azospirillum lipoferum. Furthermore, G4 and G6 endophytes isolated in LGI medium, they showed 93.8 and 94.3% identities with Klebsiella pneumoniae about nifA gene and the identity of nifH gene from H4 endophytic bacteria with in Micrococcus sp. Y70 was 97.5%. Three endophytes (A18, G4 and H4) had the best composite characteristic, they have been suggested for bio-fertilizer production.